Efektivitas Metode Diskusi pada Pembelajaran Teks Berita pada Kelas VIII - Zulfatul Maula; Agus Setyonegoro; Akhyaruddin Akhyaruddin (Jurnal Bahasa dan Sastra, 2022)
The use of learning methods that are not in accordance with the learning objectives are often an obstacle in achieving the formulated learning objectives. This research is expected to be a reference for improving and selecting effective and efficient learning methods in learning news texts at the junior high school level. The type of research used is experimental research that uses the experimental results of the pretest-posttest design. This research was conducted at Al-Azhar Junior High School IT Jambi City in February-March 2022. Based on the analysis that has been carried out, it can be said that the use of the discussion method applied to learning Indonesian for news text material results in better results than those who do not use the discussion method. The use of the discussion method can make the classroom situation in learning more effective so that it can motivate learning and the learning material will be easier for students to understand. The results of the t-test showed that there was a significant effect of the use of the discussion method on learning news texts at the junior high school level.